Morphological characteristics and yield performance of mutant soybean [Glycine max (L.) Merr.] M6 genotypes in Jatinangor, Sumedang, West Java - Andrew Yoel; Meddy Rachmadi (Jurnal Ilmu Pertanian, 2020)
Current breeding efforts in soybean largely focus on identifying genotypes with high seed yield and large seed size. Our study applied a mutation using 250 Gy Gamma-Ray Irradiation to soybean cv. Anjasari. The variability in the M1 generation was identified, and the planting was continued to M2 M3, M4, M5 until M6 generation. The objectives of this research were to evaluate mutant lines exhibiting a good performance in yield and morphological characteristics that can support the yield component in M6 generation. This research was conducted from January 2019 to May 2019 at Ciparanje Experiment Station, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, West Java. The experiment was arranged in a Randomized Completely Block Design with fifteen mutant soybean genotypes as treatments with two replications within each treatment. The results showed several genotypes produced higher yield and better agro-morphological characteristics. The genotypes MR-33, MR-4A, and MR-2A showed significantly higher number of total pods per plant. Meanwhile, the genotypes MR-35A, MR-37, MR-23, MR-36A, MR-3A, MR-29A MR-34A, MR-4A, MR-17, and MR-5A showed a higher value in weight of 100 seeds. The highest yield was observed in MR-29A and MR-23, which then will be used as the genotypes for multilocation test for stability.